Sounds of snapping shrimp (Alpheidae) as important input to the soundscape in the southeast China coastal sea - Song, Zhongchang; Ou, Wenzhan; Su, Yingnan; Li, Hongquan; Fan, Wenxin; Sun, Shengyao; Wang, Teng; Xu, Xiaohui; Zhang, Yu (Frontiers in Marine Science, 2023)
As a biological sound source widely distributed in temperate and tropical coastal waters, snapping shrimp produce strong pulses which can serve as honest signals to indicate habitat-specific soundscape. The past decade has witnessed the growing interest in investigating the acoustical activity of snapping shrimp across many shallow waters including the coastal line of the west Pacific Ocean. It was extended to the Southeast China coastal area where snapping sounds and the associated soundscape were recorded at four sites. Customized codes incorporating bandwidth and amplitude threshold operations were developed to detect snaps from the ambient noise to estimate snap rate and extract snaps individually. The subsequent analysis suggested that snaps recorded at different sites were unanimously stronger than background noise. Sound pressure level of the snaps ranged from 150 dB to 190 dB (re 1 μPa). The characteristics of snaps, including sound pressure level, duration, peak frequency, -3dB bandwidth from different sites are examined to evaluate the variability across the sites. Though snapping pulses had peak frequencies and the -3 dB bandwidth consistently below 10 kHz, snaps had considerable energy extending to the high frequency range over 200 kHz. The analysis of the acoustic data received for 7 consecutive days at one site indicated that the snap rate corresponded to tidal level periodicity. A high tide was accompanied with a local high snap rate regardless of light but this local snap rate peak was much higher at night. The mean rate fluctuated between 2000 and 4000 snaps per minute and more snaps were recorded after sunset suggesting that snapping shrimp living in the area snapped in response to light. These data may indicate that snaps are important communication means in light-limited condition and deepen our understanding on the correlation of snapping behavior and ecological environments.